2021
DOI: 10.3390/antibiotics10060742
|View full text |Cite
|
Sign up to set email alerts
|

A New Dermal Substitute Containing Polyvinyl Alcohol with Silver Nanoparticles and Collagen with Hyaluronic Acid: In Vitro and In Vivo Approaches

Abstract: The experimental use of poly (alcohol-vinyl) (PVA) as a skin curative is increasing widely. However, the use of this hydrogel is challenging due to its favorable properties for microbiota growth. The association with silver nanoparticles (AgNPs) as an antimicrobial agent turns the match for PVA as a dressing, as it focuses on creating a physical barrier to avoid wound dehydration. When associated with extracellular components, such as the collagen matrix, the device obtained can create the desired biological c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 45 publications
(43 reference statements)
3
21
0
Order By: Relevance
“…This activity was statistically different with respect to the commercial treatments and the positive control (see Figure 13 ). The antibacterial mechanism is likely related to the ability of AgNPs to disrupt bacterial cell walls and/or internalize cells to induce permanent damage of the intracellular machinery and, in turn, cause cell death [ 48 , 60 , 94 ]. Zudenina® and Microdacyn® showed a much less effective reduction of bacterial growth for Gram-positive and Gram-negative strains.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This activity was statistically different with respect to the commercial treatments and the positive control (see Figure 13 ). The antibacterial mechanism is likely related to the ability of AgNPs to disrupt bacterial cell walls and/or internalize cells to induce permanent damage of the intracellular machinery and, in turn, cause cell death [ 48 , 60 , 94 ]. Zudenina® and Microdacyn® showed a much less effective reduction of bacterial growth for Gram-positive and Gram-negative strains.…”
Section: Resultsmentioning
confidence: 99%
“…As active antimicrobial agents, Ag NPs have been dispersed in PVA hydrogels. Further improvement of tissue regeneration and wound recovery abilities have been achieved by mixing it or crosslinking it with polymers such as gelatin and hyaluronic acid, which have been thought to mimic the microenvironment of native tissues [ 48 ]. Gelatin is an animal protein obtained by hydrolysis of fibrous insoluble collagen that has been used in the synthesis of hydrogels, capsules, and microspheres for different biomedical applications, including drug delivery systems, wound dressings, and regenerative scaffolds.…”
Section: Introductionmentioning
confidence: 99%
“…The biomaterial displayed a sustained release of ibuprofen and antibacterial activity against E. coli and S. aureus [ 23 ]. As well as this, a new dermal device of polyvinyl alcohol (PVA) containing AgNPs associated with a collagen–hyaluronic acid membrane has been recently developed to promote skin regeneration, control inflammation, and reduce fungal and bacterial proliferation [ 24 ]. Besides, Haidari et al also reported a pH-responsive hydrogel for the controlled release of AgNPs in infected wounds [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…[64] Moreover, dressings were prepared using a bilayer device involving PVA-containing Ag NPs bound to collagen-HA membranes, which increases water retention and cell adhesion in vitro, and exhibits excellent skin remodeling outcomes in controlled rat skin wounds. [65] In addition, a method for manufacturing nanofiber dressings using a photo-crosslinking process without employing an organic solvent was also studied. [66] Table 3 presents recent approaches of composite materials used to improve the properties of dressings applied to hydrogels and nanofiber dressings based on PVA-HA.…”
Section: Type Composite Materials Materials Characteristicmentioning
confidence: 99%